Safeguarding Tanzania's Linguistic Heritage: Addressing The Impact of Global Integration on Natural Languages - Mhagama, Willy; Haule , J, Emmanuely; Nsyengula, P., Stephen; Wang'uba , Joel (English Lecturers and Teachers Association (ELTA), 2024)
Global integration, characterized by business activities, intermarriage, migration, tourism, and digital media glocalization, has significantly influenced language use in Tanzania. This paper investigates the diminishing space for natural languages in Mbeya, Iringa, and Njombe due to these global interactions. Using qualitative methods, the study examines the extent of linguistic genocide and proposes interventions to preserve and value natural languages. Findings underscore the urgent and immediate need for societal and familial actions to prevent the loss of linguistic heritage. The paper concludes with recommendations for policy and community initiatives to support language preservation. Keywords: Global integration: Linguistic genocide, Natural languages